Cricket Batting Test Robotic-Based Equipment Using Sensor Cameras with Grid System - Padli; Setiawan, Yogi; Soniawan, Vega; Mardela, Romi; Jonni (Journal of Education Reseach and Evaluation, 2022)
Technology development in the 5.0 era has been rapid, including in education and sports. One example of technology in sports education is a sports skills test kit. This study aims to develop and test the cricket batting test robotic-based equipment using sensor cameras with the grid system. The experiment was carried out by measuring student responses regarding using a robotic-based batting test tool using a camera sensor with a grid system. This student response is useful for knowing the extent of student responses and reactions to the products used so that they can be used as reflection material and references in designing products. The research method used in this study is Research and Development. The instrument used in this study is a test instrument in the form of an observation sheet. Product validation is divided into two, media validation and learning evaluation. The final assessment results are 160 and 162, indicating that the product is very suitable for use. They are synchronized by looking for whether there is an effect of student responses on student abilities. The results show 53,4% of the effect of students' positive responses on the object's ability. Based on the study's results, it was stated that the development of the tool was feasible to use and validated by media transfer and evaluation experts. In addition, this research is also developing research inspired by previous research. Further research is needed on implementing modified tools to see the effectiveness of training using an Android-based cricket batting test tool using a sensor camera with a grid system.